Formaldehyde and propionic acid do not reduce starch gelatinization within a laboratory setting and may not contribute to reduced pellet quality - K.M. Bowen; L.E. Knarr; E.B. Estanich; S.R. Estep; J.S. Moritz (Journal of Applied Poultry Research)
SUMMARY: Starch gelatinization acts as a pellet binder, and thereby, increase pellet quality. Increasing pellet quality has been shown to improve bird performance. The use of antimicrobial feed additives has been increasing due to the risk of salmonellosis to consumers. A previous experiment included an antimicrobial primarily composed of formaldehyde and propionic acid added at the mixer to poultry feed. The study steam conditioned the feed for a shorter duration compared to a longer duration and discovered a decrease in pellet quality. We hypothesize that the product inhibited starch gelatinization and that the degree of inhibition is based on heating time. Therefore, the objective of this experiment was to determine the effect of formaldehyde and propionic acid on starch gelatinization via glucose release and spectrophotometry across two heating times. Corn starch suspensions were heated at 82°C for 2 min 30 sec or 15 min and added to base reagents. Formaldehyde and/or propionic acid were added to the appropriate corn starch suspensions prior to heating, while the control lacked either of the chemicals. The absorbance of the 4 formulations at each heating time were measured using spectrophotometry (Beckman Coulter, DU 530, Brea, CA). Three replications were performed per treatment. All 4 formulations were analyzed using a multiple comparison. A two-way ANOVA was also employed to explore the 4 (formulation) × 2 (heating time) factorial arrangement of treatments. There was a heating time × formulation interaction where all formulations heated for 15 min had a significant increase in gelatinization relative to the 2.5 min formulations, with the control formulation showing the least amount of change (P < 0.05). Formaldehyde and propionic acid did not reduce starch gelatinization regardless of heating time. The increase in starch gelatinization with increased heating time may translate to increasing pellet quality.